Angola : Second Post-Program Monitoring. (IMF Staff Country Reports; Country Report ;, 2014)
This paper reviews Angola's Second Post-Program Monitoring for different economic developments and policies. The IMF report highlights that Angola has returned to a path of solid economic growth, with single-digit inflation, a strong international reserves position, and a stable exchange rate. Growth has slowed to 4 percent in 2013, but is expected to increase to 5 percent in 2014 as oil production recovers. It outlines that Angola's capacity to repay the fund remains strong, but the macroeconomic framework and institutional setting should be strengthened to facilitate the process of rebuilding external and fiscal buffers.